Case Report of Fibro-Adipose Vascular Anomaly (FAVA) with Activating Somatic PIK3CA Mutation. (2nd August 2022) - Driskill, Jordan H.; Hwang, Helena; Callan, Alexandra K.; Oliver, Dwight
Abstract : Fibro-adipose vascular anomaly (FAVA) is a recently described complex and painful benign lesion found in young adults and the pediatric population composed of intramuscular vascular, fibrous, and adipose tissues. A previous report has identified the presence of somatic mosaic mutations in the gene for the catalytic subunit of phosphatidylinositol 3-kinase ( PIK3CA ) in cases of FAVA. Herein, we present a case of FAVA found in a 23-year-old male patient who presented with chronic wrist pain associated with a mass, and we identified an associated somatic activating mutation (H1047R) in PIK3CA . We briefly review the relevant literature surrounding the identification and histology of FAVA, the known mutational spectrum, downstream signaling pathways, and relevant treatment modalities. Our case highlights the association between FAVA and somatic mosaic activating PIK3CA mutations.